DEVELOPING HOTS-BASED E-MODULE TO IMPROVE STUDENTS’ READING SKILL AT SATU NUSA LAMPUNG UNIVERSITY - Maiza, Masfa; Amanah, Firma Pradesta; Nafi'ah, Homsatun (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2024)
The rapid development of technology supports a creative and innovative educational process in digital form, especially in providing digital material. E-module, as one of the digital materials, allows the students to access it easily. This research aims to develop a Higher Order Thinking Skill (HOTS)-based e-module of reading for English Literature students at Satu Nusa Lampung University. This teaching material is developed using Canva. This uses the ADDIE research and development (R&D) model in five stages, namely (1) Analysis (2) Design (3) Development (4) Implementation, and (5) Evaluation. The result shows that this e-module that has been developed is valid, practical, and effective. The validity of this e-module reaches a very good category based on the expert’s and validator’s evaluation.  The practicability reaches very good based on the students’ responses and lecturers’ evaluation. This e-module is effective and reaches a very good category based on the students’ achievement on the test.